Peningkatan Efektivitas Pemberian Nutrisi untuk Produksi Benih Kentang Sistem Aeroponik pada Gabungan Kelompok Tani Cikandang Agro, Desa Cikandang, Cikajang, Garut - Handarto Handarto; Muhammad Saukat; Mimin Muhaemin (Institut Pertanian Bogor, 2025)
The three priority issues faced by the Cikandang Agro Farmers Group are 1) the flow of nutrient solution is not smooth due to clogged nozzle holes and the insoluble nutrient solids; 2) the misting flow of the nutrient solution is uneven due to leaks at several points in the nutrient solution distribution pipes; and 3) not all root zones of the plants are reached by the nutrient spray due to the nutrient solution spray not being in the form of fog. The objectives of the activity are 1) to design and to construct a system device for preparing and atomizing nutrient solutions for the production of potato seeds in an aeroponics system; and 2) improve the performance of nutrient solution preparation and atomization system devices for potato seed production aeroponics system. The implementation of activities consists of program socialization, training/technical guidance, application of technology, as well as monitoring and evaluation. The substance of the activity consists of problem and need analysis, design and assembly, as well as operation and performance tests. Success indicators were observed through pre-test and post-test which included domains of the cognitive and psychomotor of participants in mastering the technology of preparation and atomization of nutrient solutions for the production of potato seeds in the aeroponics system. Based on the evaluation through pre-test and post-test, there was an increase in the cognitive domain by 80% and psychomotor domain by 70% of participants in mastering the technological aspects of preparation and atomization of nutrient solutions for the production of potato seeds of the aeroponics system. Technical improvements to the equipment of the nutrient solution preparation and fog system produce a smooth flow of nutrient solution, and the nutrient solution spray is no longer in the form of mist but in the form of a uniform fog and is able to reach the plant root zone.